Long‐Range Cationic Disordering Induces two Distinct Degradation Pathways in Co‐Free Ni‐Rich Layered Cathodes. (16th January 2023) - Hua, Weibo; Zhang, Jilu; Wang, Suning; Cheng, Yi; Li, Hang; Tseng, Jochi; Wu, Zhonghua; Shen, Chong‐Heng; Dolotko, Oleksandr; Liu, Hao; Hung, Sung‐Fu; Tang, Wei; et al.
Abstract: Ni‐rich layered oxides are one of the most attractive cathode materials in high‐energy‐density lithium‐ion batteries, their degradation mechanisms are still not completely elucidated. Herein, we report a strong dependence of degradation pathways on the long‐range cationic disordering of Co‐free Ni‐rich Li1− m (Ni0.94 Al0.06 )1+ m O2 (NA). Interestingly, a disordered layered phase with lattice mismatch can be easily formed in the near‐surface region of NA particles with very low cation disorder (NA‐LCD, m ≤0.06) over electrochemical cycling, while the layered structure is basically maintained in the core of particles forming a "core–shell" structure. Such surface reconstruction triggers a rapid capacity decay during the first 100 cycles between 2.7 and 4.3 V at 1 C or 3 C. On the contrary, the local lattice distortions are gradually accumulated throughout the whole NA particles with higher degrees of cation disorder (NA‐HCD, 0.06≤ m ≤0.15) that lead to a slow capacity decay upon cycling. Abstract : A series of Ni‐rich Li1− m (Ni0.94 Al0.06 )1+ m O2 (NA) oxides are synthesized through tailoring the heating temperature. The NA oxides with high cation disorder experience a comparably homogeneous fatigue process upon extended cycling, while a disordered surface with lattice mismatch is gradually formed in the NA with low cation disorder (i.e. heterogeneous degradation) which results in a rapid capacity decay during the fast charge–discharge cycling.